Preoperative prognostic factors for weight-loss after adjustable gastric banding: 5-year results of randomized controlled trial - Juodeikis, Žygimantas; Brimas, Gintautas (Lietuvos chirurgija, 2017)
Background Laparoscopic adjustable gastric banding (LAGB) is used as a bariatric procedure for more than 30 years, but there is still insufficient data regarding postoperative weight-loss predicting factors. Objective We carried out a prospective randomized study to compare two different bands (SAGB and Minimizer Extra) and aimed to find weight-loss predicting factors. Methods A total of 103 morbidly obese patients underwent LAGB from January 2009 to January 2010. The SAGB was used in 49 and MiniMizer Extra in 54 patients. Weight loss was evaluated after 1 and 5 years. Factors which significantly correlated with percentage excess weight loss (%EWL) were used to build predicting regression models. Results The mean patient age was 45.9 ± 11.7 years, and mean preoperative body mass index (BMI) was 47.5 ± 7.3 kg/m2. A total of 90 (87.3%) patients completed the 5-year follow-up. The mean overall excess weight loss after 5 years was 47.3 ± 29.7%, and there was no difference between SAGB and MiniMizer bands (47.3% vs 50.3%; p = 0.14). After 1 year, BMI ≤ 47 MiniMizer, patients demonstrated better weight loss results. %EWL was also significantly greater in >40-year-old MiniMizer group patients (p =0.012) and remained significantly higher after 5 years (p = 0.035). Conclusions In > 40-year-old patient group better %EWL can be achieved by using MiniMizer Extra bands compared to SAGB. The constructed prognostic models could be used to predict %EWL after application of SAGB and MiniMizer bands.